2009
DOI: 10.1080/08927020802412370
|View full text |Cite
|
Sign up to set email alerts
|

Sorption strains and their consequences for capillary condensation in nanoconfinement

Abstract: We employ Monte Carlo simulations in a semi-grand canonical ensemble to investigate the impact of pore deformation on capillary condensation in nanoconfined fluids. The fluid is composed of 'simple' spherically symmetric molecules of the Lennard-Jones type. These molecules are confined to a slit pore, where the pore walls consist of a single layer of atoms distributed according to the (100) plane of the face-centred cubic lattice. The atoms are bound to their equilibrium lattice sites by harmonic potentials su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…As pressure increases, CO 2 molecules try to enter the pores leading to higher pore filling degree and densification. The solvation pressure depends on the pore width and fluid pressure and it increases with increasing fluid pressure and decreases with increasing pore width [51,52]. At pressure P/P sat~0 .3 the pore width exceeds twice the diameter of the CO 2 molecules.…”
Section: Origin Of Deformation Of Microporesmentioning
confidence: 99%
“…As pressure increases, CO 2 molecules try to enter the pores leading to higher pore filling degree and densification. The solvation pressure depends on the pore width and fluid pressure and it increases with increasing fluid pressure and decreases with increasing pore width [51,52]. At pressure P/P sat~0 .3 the pore width exceeds twice the diameter of the CO 2 molecules.…”
Section: Origin Of Deformation Of Microporesmentioning
confidence: 99%
“…They found that pores can both expand and contract, depending on the pore size and pressure of the adsorptive gas. Gunther and Schoen [26,27] have employed computer simulation to study the effects of the capillary condensation of simple L-J molecules on the behaviour of model deformable solids and also found that both expansion and contraction could occur as the adsorbate pressure moves through the transition region. Neimark and co-workers have used density functional theory to study methane and carbon dioxide adsorption in carbons under very high pressures as a model system for sequestration in coal seams [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, κ is a measure of rigidity of the substrates. For values of κ used below we utilized a modified Lindemann criterion to ensure that over the temperature ranges studied the solid substrates do in fact not melt [30]. Hence, in the system of interest the total configurational energy may be expressed as [see Eqs.…”
Section: Model Systemmentioning
confidence: 99%